LEASING AS FORM OF STATE-PRIVATE PARTNERSHIP - E. B. Zavyalova; I. V. Linev (Vestnik MGIMO-Universiteta)
In economy of a number of foreign countries alternatively privatizations of objects, the publicprivate partnership (PPP) concept is widely applied. Interaction of the state and business is characteristic feature of modern mixed economy. The specified partnership is realized with use of diverse models and can accept various forms. The task consists in choosing such form (a legal ground of realization of concrete model) at which PPP will be the most rational and effective. The leasing possessing financial, investment, organizational and operational, service, practical and other advantages, represents one of the most acceptable PPP forms, for realization in modern conditions of domestic economy. The specified advantages of the parties of the contract of leasing and its fundamental difference from the rent, being that when leasing the private sector, entering partnership with the state, not only applies administrative skills, but also invests the capital, are preconditions for its widespread introduction. At the same time, as a whole positive dynamics of development of the market of leasing in the Russian Federation has no steady character. The situation can be broken if return of invested funds is guaranteed to the investor (including foreign) and it will have an opportunity to profit. As the option of a solution is offered to apply non-standard approaches at implementation of leasing operations, in particular - with scoring use. It is necessary to emphasize that application of scoring most effectively when the leasing market is on lifting and demanded there is an efficiency of an assessment of the project and a standart of procedures, and the speed of service of the participants of the leasing contract plays one of leading roles. This advantage, becomes a shortcoming at the current situation in the market when more weighed assessment of risks is required, and for this reason skoring models demand continuous completion and updating with frequency of times in one and a half-two years. Leasing application as the PPP forms, not only the professional experience, effective management, flexibility and efficiency in decision-making will provide, ability to innovation, but also will provide serious investment activity. It in turn will allow to introduce new equipment and more effective technologies, to create the new enterprises, on a labor market to increase demand for highly skilled workers.